The Treatment of Oesophageal Perforation after Anterior Cervical Spinal Surgery. (1st April 2019) - Hu, Li-Sheng; Wu, Zhen-Quan; Zou, Li-Min; Huang, Yong-Can
Abstract : Oesophageal perforation is a rare complication occurring during or after cervical spine surgery, and the risk factors are not well understood. This study presents a case of a 25-year-old man with oesophageal perforation after anterior cervical spine surgery. It is suggested that four factors (anatomical structure, mechanism of trauma, implant dislodgment, and the operation) could induce postoperative oesophageal perforation after cervical spine surgery performed using the anterior surgical approach. A comprehensive understanding and early management of this complication are necessary for successful therapy.